The Farmer Has the Wheat—but Where is the Bread? - Chester J. Teller (Journal of Applied Communications, 1971)
Speaking before the Dairy Industry Association at Burlington, Vermont, last September, Under Secretary of Agriculture J. Phil Campbell said, "No other major American industry has ever operated with such little concern for the market as has been the case with American agriculture."